2022
DOI: 10.1186/s12889-021-12387-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and trends in Australian adolescents’ adherence to 24-hour movement guidelines: findings from a repeated national cross-sectional survey

Abstract: Background 24-hour movement guidelines recommend a healthy balance of high levels of physical activity, low levels of sedentary behaviour and appropriate sleep duration each day. At present, surveillance data on how Australian adolescents are performing against these guidelines are lacking. This study aims to describe the extent to which Australian secondary school students are adhering to the physical activity, sedentary recreational screen time and sleep duration recommendations outlined in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
4
13
1
Order By: Relevance
“…Other nations are experiencing similar public health concerns related to declining movement behavior guideline adherence as evidenced by a recent study of Australian adolescents. 33 Together, these findings extend upon previous work that has investigated MVPA, recreational ST and sleep trends independently, each showcasing less favorable outcomes. [34][35][36] Taking an integrative approach rooted in the 24-h movement paradigm represents a strength of the present study as more evidence emerges demonstrating the need to consider the co-dependence among these behaviors and how they interact to influence health.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Other nations are experiencing similar public health concerns related to declining movement behavior guideline adherence as evidenced by a recent study of Australian adolescents. 33 Together, these findings extend upon previous work that has investigated MVPA, recreational ST and sleep trends independently, each showcasing less favorable outcomes. [34][35][36] Taking an integrative approach rooted in the 24-h movement paradigm represents a strength of the present study as more evidence emerges demonstrating the need to consider the co-dependence among these behaviors and how they interact to influence health.…”
Section: Discussionsupporting
confidence: 77%
“…Even so, findings of this study present a significant health threat, as ample evidence has demonstrated the strong association between 24‐h movement guideline adherence and various health outcomes 2 . Our study provides an impetus for the development of effective health promotion strategies that take an integrative approach targeting MVPA, recreational ST and sleep simultaneously, as there is evidence suggesting a declining trend in rates of 24‐h movement guideline adherence 33 …”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Welfare Evans-Whipp & Gasser, 2019;Friel et al, 2020;Gomes et al, 2017;Grady et al, 2018;Hui et al, 2021;Olds et 2018;Roberts et al, 2017;Roman-Viñas et al, 2016;Scully et al, 2022;Tooth et al, 2019), adherence to individual guidelines varied by movement behaviour, with 44%, 18% and 88% of families having all children meeting ST, PA and sleep guidelines, respectively.…”
Section: Consistent With Other Research (Australian Institute Of Heal...mentioning
confidence: 99%
“…Adherence to sleep guidelines tends to be the highest of the three behaviours, particularly in younger children (Grady et al, 2018;Scully et al, 2022), possibly reflecting the biological necessity of sleeping and that it tends to occur within the home. Meeting ST and PA guidelines has found to range from 5% to 87% (Cooper et al, 2015;Gomes et al, 2017;Olds et al, 2018;Roman-Viñas et al, 2016;Telford et al, 2013).…”
Section: Consistent With Other Research (Australian Institute Of Heal...mentioning
confidence: 99%